Party nationalization following democratization: modelling change in turbulent times. Issue 6 (19th September 2017) - Mustillo, Thomas
ABSTRACT: Which political parties grow more or less statically nationalized in the immediate aftermath of a democratic transition? What accounts for these changes? This is the first broadly cross-national analysis of this dimension of stabilization of the democratic regime. It uses a sample of 64 moderate and large political parties from 19 countries in South Europe and Latin America. In the first stage of the analysis, I use growth curve models on panels of district-level, lower house, election results to test each party for changes in static nationalization. Results show that 41% of the cases grow more nationalized, about 22% grow less nationalized, and the rest show no evidence of change. Then, I test explanations of increasing static nationalization derived from (a) the competitive context; (b) the institutional context; and (c) the social structural context. I find that parties become more nationalized when (a) they are jointly programmatic and in government, and the party system is less fragmented; (b) the political system is centralized and a presidential election is concurrent; and (c) society is less ethnically fragmented. Finally, I confirm that more statically nationalized parties are associated with a higher quality of democracy.